Follow-up C-reactive protein level is more strongly associated with outcome in stroke patients than admission levels - Rocco, Andrea; Ringleb, Peter A.; Grittner, Ulrike; Nolte, Christian H.; Schneider, Alice; Nagel, Simon (Neurological sciences, 2015)
The value of C-reactive protein (CRP) as a prognostic tool in stroke patients is unclear. The aim of this study is to explore the prognostic impact of CRP levels assessed at different time points on functional outcome in a large cohort of thrombolysed acute stroke patients. All thrombolysed stroke patients admitted to our department were entered in an open, prospective database. Clinical and demographic data were recorded. CRP was measured upon admission, within 24 h, and in the following days. Functional outcome was assessed using the modified Rankin Scale (mRS) at 3 months. Among 1242 thrombolysed patients, we found a statistically significant difference in median CRP values upon admission, within 24 h, and follow-up with respect to outcome parameters (p < 0.001) including symptomatic intracerebral hemorrhage (sICH; p < 0.001). In regression models, follow-up CRP showed better predictive properties for outcome parameters compared to CRP assessed upon admission or within 24 h. The ROC analysis showed a good predictive value of follow-up CRP concerning dependent outcome [c-statistic 0.71 (95 % CI 0.67-0.75) p < 0.001] and mortality [c-statistic 0.70 (95 % CI 0.66-0.75) p < 0.001]. After adjustment for risk factors, follow-up CRP, but not admission CRP, was independently associated with dependent outcome (OR 2.67, 95 % CI 1.76-4.06; p < 0.001), mortality (OR 2.53, 95 % CI 1.50-4.25; p < 0.001), and sICH (OR 3.03, 95 % CI 1.51-6.06; p = 0.002). Follow-up CRP is strongly associated with functional outcome, sICH, and mortality after 90 days in thrombolysed stroke patients.